Optimizing manual web accessibility evaluation through a specialized tool - Salton, Bruna Poletto; Dall Agnol, Anderson; Nervis, Lael; da Silva, Tiago Silva; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Although the most widely used and studied web accessibility assessment methods involve only automated testing, this type of testing has limitations and does not provide completely reliable results. A complete assessment can only be achieved through a manual review that involves specialists and people with disabilities. However, performing manual accessibility testing as a team might be challenging regarding reporting errors, combining results, and managing the process. This paper details the usage of a tool designed to support the manual web accessibility evaluation process, highlighting its specifications and functionalities, as well as presenting the testimonies of team members - testers with disabilities and specialists. The results show that both testers and specialists had an overall positive experience using the tool, indicating it helps increase confidence in reporting, facilitates the workflow, and makes the process more efficient. Although the results indicate that the tool effectively supports the evaluation process, other features can be implemented to make some tasks less time-consuming, and more tests need to be performed to identify other possible improvements and verify the tools’ potential in different contexts.